Globalization And It’s Impact On Higher Education In Indonesia - Nurwahida Nurwahida (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2019)
This study provides an overview of the influence of globalization on higher education in Indonesia. Globalization has brought positive effects on education as it has led to some changes including the characteristics of higher education in Indonesia, the number of students studying abroad as well the effort to improve human resource through teacher training. The major characteristics changed in education system is that the integration of technology in teaching and learning process. Enabling the implementation of ICT in education will improve the quality of teaching as well elevate students learning experience in and outside the classroom. Besides, the ability to access any information easily todays has influenced the increasing number of students studying abroad. The last but not the least, globalization has contributed the development of human resources in Indonesia. These changes are expected to enable the teachers and students to learn and get information about the recent issue in the world.